The evaluation on metabolic syndrome and nutrition in patients with schizophrenia - Şanlıer, Nevin; Ayyıldız, Feride; Urhan, Murat; Toka, Onur (Progress in Nutrition, 2019)
The prevalence of metabolic syndrome (MetS) in patients with schizophrenia is increasing as is most diseases. It was aimed to assess eating habits, dietary intake, physical activity status and body composition which are important risk factors for MetS among patients with schizophrenia and compare with a healthy control group in this study. 32 patients with schizophrenia and 32 healthy controls aged 18-60 years were participated between September 2014-May 2015 in Turkey. The classification of MetS was examined by using three different methods. There wasn’t any individuals in healthy control group who was diagnosed as MetS according to different MetS criterias. However the rate of MetS in patients with schizophrenia was high (43.8-46.9%). Their body weight, body mass index (BMI), fat mass, waist circumference, waist-hip ratios were also higher than the healthy control group (p